2012
DOI: 10.3109/10826084.2012.663283
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Tobacco, and Prescription Drugs: The Relationship With Illicit Drugs in the Treatment of Substance Users

Abstract: Alcohol, tobacco, prescription drug, and illicit drug use frequently co-occur. This paper reviews the extent of this co-occurrence in both general population samples and clinical samples, and its impact on treatment outcome. We argue that the research base for understanding comorbidity among tobacco, alcohol, prescription, and illicit drugs needs to be broadened. We specifically advocate for: (1) more epidemiological studies of relationships among alcohol, tobacco, and other illicit drug use; and (2) increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 90 publications
2
4
0
Order By: Relevance
“…In agreement with previous reviews, 8 , 9 , 10 , 11 , 12 this study found that hazardous or harmful or probable dependent alcohol use among both men and women, having had more than one sexual partner in the past 12 months among men, having been victim of violent crime among men and psychological distress (anxiety and depression) among women were associated with drug use. Drug use prevention and intervention have to include co-morbidity factors such as common mental disorders, alcohol use disorders and sexual risk behaviour.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous reviews, 8 , 9 , 10 , 11 , 12 this study found that hazardous or harmful or probable dependent alcohol use among both men and women, having had more than one sexual partner in the past 12 months among men, having been victim of violent crime among men and psychological distress (anxiety and depression) among women were associated with drug use. Drug use prevention and intervention have to include co-morbidity factors such as common mental disorders, alcohol use disorders and sexual risk behaviour.…”
Section: Discussionsupporting
confidence: 92%
“…Previous investigations in South Africa and other countries found that specific sociodemographic factors were associated with drug use, including male gender, 5 , 6 younger age, 5 specific population groups (mixed race and white people), 5 , 6 lower income or not employed 5 and geolocality such as urban areas. 5 , 7 Further, certain health risk behaviours such as common mental disorders (major depression and anxiety disorders), 8 , 9 alcohol use disorders, 10 HIV risk behaviours 11 and criminal victimisation 12 have been found to be associated with drug use.…”
Section: Introductionmentioning
confidence: 99%
“…Those with alcohol use disorder and those who have reported other drug use were signi cantly associated with daily and nondaily cannabis use. These nds are similar to other research where it would seem that cannabis and alcohol usage are interlinked [7,11,12,14,36] as well as cannabis and other drug usage [11,12]. Interestingly, the adjusted logistic regression showed that among cannabis users, other drug use had lower odds of daily cannabis use and could be due to other drug users not considering cannabis as their primary drug.…”
Section: Discussionsupporting
confidence: 89%
“…Of note, the high rate of smoking and drinking in our results was in line with previous studies in the mountainous region of Vietnam [ 16 , 17 ]. The comorbidity of tobacco, alcohol and drug addiction has been observed in prior literature [ 18 ]. As alcohol and tobacco dependencies are associated with a higher risk of HIV/AIDS contraction [ 19 ], our study embraces the necessity of integrating alcohol and tobacco screening and counseling programs in methadone treatment.…”
Section: Discussionmentioning
confidence: 99%